Goodbye, CRT. - O'Donovan, P.
With many developed countries going fully digital in the near future, the entire television landscape is expected to change dramatically in the next few years. Plasma and LCDs as well as several new technologies including the surface-conduction electron-emitter display (SED) are vying to replace the 100-year old CRT. After examining the advantages and disadvantages each of these new options, the paper predicts that LCD televisions will dominate by 2010
Keywords: CRT; TV display dominance; Cathode-ray tube; Flat-screen systems; High-definition video; Liquid crystal display technology; Picture quality; Plasma televisions; Power consumption; Projection television; Surface-conduction electron-emitter display